2021
DOI: 10.29313/mimbar.v37i2.8055
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Loyalty as Impact of Marketing Mix and Customer Satisfaction

Abstract: This study aims to analyze the influence of the marketing mix consisting of products, prices, places and promotions as one of the marketing strategies at Solata Cafe Palopo. The population in this study is Solata Cafe Palopo customers with a sampling technique using purposive sampling and data obtained by distributing questionnaires to 100 respondents. The method used in this study is the evaluation of SEM models using Partial Least Square (PLS). Results of the study show that product, place and promotion vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The results are consistent with the previous studies which revealed that customers satisfaction mediates the relationship between MM and customers' loyalty (Sukamto and Lumintan, 2015;Saneva and Chortoseva 2020;Thanabordeekij and Syers, 2020;Xie, 2020;Hutauruk et al, 2020;Grace et al, 2021;Risal and Aqsa, 2021;Mukarromah et al, 2021;Raharjo and Digdowiseiso, 2022) In the same vein as the results, Mokhtar and Sjahruddin (2019) revealed that customers' satisfaction is playing a mediating role in the impact of service quality on customers' loyalty. Pi and Huang (2011) revealed that promotions significantly impact satisfaction and trust which are affecting the customers' loyalty.…”
Section: Mediation Role Of Customers' Satisfaction (H4)supporting
confidence: 91%
See 1 more Smart Citation
“…The results are consistent with the previous studies which revealed that customers satisfaction mediates the relationship between MM and customers' loyalty (Sukamto and Lumintan, 2015;Saneva and Chortoseva 2020;Thanabordeekij and Syers, 2020;Xie, 2020;Hutauruk et al, 2020;Grace et al, 2021;Risal and Aqsa, 2021;Mukarromah et al, 2021;Raharjo and Digdowiseiso, 2022) In the same vein as the results, Mokhtar and Sjahruddin (2019) revealed that customers' satisfaction is playing a mediating role in the impact of service quality on customers' loyalty. Pi and Huang (2011) revealed that promotions significantly impact satisfaction and trust which are affecting the customers' loyalty.…”
Section: Mediation Role Of Customers' Satisfaction (H4)supporting
confidence: 91%
“…According to Risal and Aqsa (2021), factors related to product, place, and promotion have a significant effect on CS, which in turn has a significant impact on CL. According to Grace et al (2021), CS has a positive and significant influence on CL, and product quality has a significant impact on CL.…”
Section: The Mediating Role Of Customers' Satisfaction On the Relatio...mentioning
confidence: 99%